2019
DOI: 10.1017/s0950268818003667
|View full text |Cite
|
Sign up to set email alerts
|

Development of predictive nomograms for clinical use to quantify the risk of isolating resistance prone organisms in patients with infected foot ulcers

Abstract: Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus (MRSA) have been considered prevalent pathogens in foot infections. However, whether empiric therapy directed against these organisms is necessary, and in whom to consider treatment, is rather unclear. The aim of this study was to develop predictive algorithms for forecasting the probability of isolating these organisms in the infected wounds of patients in a population where the prevalence of resistant pathogens is low. This was a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A history of MRSA was the only risk factor significantly associated with MRSA DFIs, though MRSA nasal colonization approached significance ( P = .07); both risk factors have been reported previously [ 3 , 5 ]. Notably, MRSA nasal colonization has been characterized as an insensitive but specific predictor of MRSA in DFIs [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…A history of MRSA was the only risk factor significantly associated with MRSA DFIs, though MRSA nasal colonization approached significance ( P = .07); both risk factors have been reported previously [ 3 , 5 ]. Notably, MRSA nasal colonization has been characterized as an insensitive but specific predictor of MRSA in DFIs [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 68%
“…In this survey of DFI cultures, MRSA was less prevalent than literature values (10%–20%) [ 3 , 4 ], whereas PsA was more prevalent (5%–10%) [ 5–7 ]. In the case–control study, a history of MRSA was associated with MRSA DFIs, and the presence of gangrene was associated with PsA DFIs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another retrospective study showed that a history of MRSA infection (OR 5.6, 95% CI 1.56–20.63) and osteomyelitis (OR 2.5, 95% CI 1.00–6.79) was linked to a higher chance of MRSA isolation (C statistic of 0.7). Previous work also introduced a predictive nomogram with moderate to good discrimination for MRSA infection in patients with infected foot ulcers [ 23 ]. In this study, we developed a model and used the bootstrap method to validate the nomogram with an AUC value of 0.70 and a sensitivity of 92.39% at a threshold of 0.3 in the dataset ( Figure 2 and Figure 3 A,B and Table 3 ).…”
Section: Discussionmentioning
confidence: 99%